2005
DOI: 10.1016/j.dsr.2005.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Development and deployment of a precision underwater positioning system for in situ laser Raman spectroscopy in the deep ocean

Abstract: The fie ld of ocean geochemistry has recently been expanded to include in situ laser Raman spectroscopic measurements in the deep ocean. While this technique has proved to be successful for transparent targets, such as fluids and gases, d iff iculty ex ists in u sin g deep sub mergence vehicle man ipulators to position and control the very small laser spot with respect to opaque samples of interest, such as many rocks, minerals, bacterial mats, and seafloor gas hydrates.We have developed, tested, and successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 9 publications
1
34
0
1
Order By: Relevance
“…Due to the small depth of focus of all of the sampling optics described, some form of positioner will be required to locate the laser spot on the target of interest. The three-degree-of-freedom Precision Underwater Positioner (White et al, 2005) developed for the DORISS instrument is an example of the type of system needed. For long-term Raman deployments at hydrothermal vents, positioning will be a challenge, as vent deposit topography can change rapidly over time.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Due to the small depth of focus of all of the sampling optics described, some form of positioner will be required to locate the laser spot on the target of interest. The three-degree-of-freedom Precision Underwater Positioner (White et al, 2005) developed for the DORISS instrument is an example of the type of system needed. For long-term Raman deployments at hydrothermal vents, positioning will be a challenge, as vent deposit topography can change rapidly over time.…”
Section: Resultsmentioning
confidence: 99%
“…Laboratory Raman studies of individual shells have shown the presence of calcite and/or aragonite. In situ laser Raman spectroscopy measurements have also identified calcite and aragonite in shells on the seafloor (White et al, 2005;White et al, 2006b).…”
Section: Carbonatesmentioning
confidence: 99%
See 3 more Smart Citations